Jual Beli Online Dengan Menggunanakan Sistem Dropshipping dalam Perspektif Hukum Islam - Ubaidillah, Ubaidillah (MOMENTUM : Jurnal Sosial dan Keagamaan, 2022)
Over time, e-commerce has developed very rapidly in terms of innovative buying and selling transactions, one of which is a dropshipping buying and selling transaction model. This transaction model invites several ikhtilaf scholars regarding the validity of the transaction. Therefore, it is necessary to observe more deeply about its legal status, bearing in mind that in buying and selling, the object of sale and purchase (المبيع ) must at least be owned by the seller in advance, both in muamalah fiqh law and in statutory regulations, because in positive law nothing is explicitly stated. directly regulates the sale and purchase of dropship. To answer the problems that exist in this study, the researchers used a descriptive qualitative research method. Data collection techniques in this study used interviews and observation. Then the data obtained were analyzed using data verification. Based on the results of the discussion, buying and selling with the dropship system in the view of Islamic law is permissible if the contract uses a wakalah contract